A Literature Review on the Mental Health and Coping Strategies of Healthcare Workers in This Time of Pandemic - Aclon, Ma-Ai C.; Perez-Ambray, Ma. Chelsea; Antiporda, Mae Cherryrose P.; Dizon, Maria Pia S.; Garcia, Paul Reinald B.; Lapitan, Marie Anne A.; Nocos, Purisima M.; Aquino, Sherwin S.; Parico, Aristotle M.; Lopez, Mary Ann E.; Guevarra, Cecile F.; Orte, Christian Jay S.; Floresca, Hanna Monique A.; Jecino, Liza May B.; Ruiz, Fred B. (Future Science / FSH-PH Publications, 2022)
This literature review focused on the mental health and coping strategies of healthcare workers amidst pandemic. Coronavirus disease 2019 (COVID-19) has produced a worldwide health catastrophe that has mandatory emergency protocols and control in all countries. The increasing number of confirmed positive patients and deaths has caused health emergency to health care providers and even to the health system. Besides the population that had been infected, healthcare workers who are at the forefront of battling with the disease have also been ill. The fact that nurses have longer exposure, a revealing misery associated to mental health issues such as depression, drowsiness and sleep deprivation was fabled. As many people would say nowadays, “depression is real” and this opens gates as this study aims to explore on the mental health status of the healthcare workers and their coping strategies as identified by several studies.